2018
DOI: 10.1021/acsomega.8b02438
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Silver Nanoclusters as Potent Antimicrobials against Multidrug-Resistant Bacteria

Abstract: Bacterial multidrug resistance (MDR) is a serious healthcare issue caused by the long-term subtherapeutic clinical treatment of infectious diseases. Nanoscale engineering of metal nanoparticles has great potential to address this issue by tuning the nano–bio interface to target bacteria. Herein, we report the use of branched polyethylenimine-functionalized silver nanoclusters (bPEI–Ag NCs) to selectively kill MDR pathogenic bacteria by combining the antimicrobial activity of silver with the selective toxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…Below 250 × 10 −9 m , the antibiofilm activity of AgNPs became less prominent while the bacteria remained intact. At concentrations higher than 1 × 10 −6 m , the bactericidal activity of AgNPs eliminated the availability of viable bacteria from establishing biofilm . The in vitro anti‐FapC activities of AgNPs/AgNCs were correlated with their antibiofilm activity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Below 250 × 10 −9 m , the antibiofilm activity of AgNPs became less prominent while the bacteria remained intact. At concentrations higher than 1 × 10 −6 m , the bactericidal activity of AgNPs eliminated the availability of viable bacteria from establishing biofilm . The in vitro anti‐FapC activities of AgNPs/AgNCs were correlated with their antibiofilm activity.…”
Section: Resultsmentioning
confidence: 99%
“…Cationic bPEI was employed to graft two types of Ag nanostructures ( Figure A,B) by chemical reduction . The size, morphology, and zeta potential of the nanoparticles are summarized in Figure 1C–H.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the MIC of silver nanoclusters functionalized with branched polyethylenimine (bPEI−Ag NCs) was defined against twelve pathogenic MDR bacteria [49]. The results revealed that a 10 to 15-fold lower MIC was found for nanoparticles than that of PEI and from two to three times lower than that of lonely silver nitrate and the noticed wide range antibacterial activity can be assigned to the positive character of hydrophobic surface ligands that simplify the action of bPEI−Ag NCs with bacterial cells that initiates membrane injury, besides liberation of silver ions from the nanocluster compound [49]. By using a new seed growth synthesis, the coating of bulk glass materials with silver nanoplates was achieved.…”
Section: Polymer Stabilized Nanomaterialsmentioning
confidence: 99%